O tratamento do verbo nos livros didáticos de Ensino Fundamental II - Christien, Stéphanie (2015)
This research addresses the issue of grammar teaching in the final years of public elementary schools, specifically focusing on the teaching of verb proposed in textbooks adopted in the triennium 2014-2016. To do this, we analyzed two (2) collections approved by the National Textbook Program (PNLD / 2014). Presented equally by the 'Guide to textbooks: PNLD 2014 - Portuguese: elementary school - final years', the two collections selected for analysis turn out to be the 1st (first) and the 12th (twelfth - that is, the last ranking) more requested for procurement and distribution in public schools across the country. The research adopts the perspective proposed by Travaglia (2011) that the activities of teaching / learning grammar - which should focus mainly on the development of the communicative competence of students - must focus on the analysis of linguistic conditions of significance and of production effects of significance as well as the grasp - not necessarily explicit - and proper handling of such significance conditions. Thus, this study aims to undertake a literature review concermimg the four semantic categories of the verb, namely: the mode, the time, the aspect and the voice, correlating them to non-nominal verb forms (temporal-modal inflections and periphrases/ verb phrase) that encode them for, later, apprehend - in the analyzed corpus - differences concerning the verb teaching and its grammatical conditions of significance. Based on Applied Linguistics for Native Language Teaching and Learning, the research also proposes to indicate topics on verb that could/should be addressed but are ignored by textbooks. Choosing the theoretical-practical methodology, this research is mainly a documentary analysis. This comes with extensive literature research to support (i) the theoretical choices regarding nomenclature, the conceptualization and the subdivision of the four semantic categories of the verb and (ii) the choice of terminology of the morphotax of Portuguese language the most appropriate possible. The research verified the perspective that textbooks have, nowadays, internal inconsistencies and incoherencies and elucidated the need for a scientific theory of linguistic phenomena with an outlook already facing its didactization, e.g, building a bridge between linguistic and applied linguistics, which is, in our view, the only path that can lead to the long-awaited renewal of language education.